Assessment of predictors and mitigation strategy for therapeutic inertia in the management of hypertension: a quality improvement project - Ananyan Sampath; Shreya Deshpande; Rashmi Verma; Rajnish Joshi (Future Healthcare Journal)
Introduction: Hypertension remains a leading cause of global morbidity and mortality, with prevalence exceeding 1.4 billion and rising, particularly in low–middle income countries (LMICs).1,2 Despite extensive guidelines, therapeutic inertia (TI) impedes optimal blood pressure (BP) control, contributing to poor outcomes.3 Hypertension prevalence in India is rising, but awareness, treatment and control lag due to patient factors, poor health awareness, clinical latency and physician prescribing behavior, leaving over 90% of patients with uncontrolled BP.4 Materials and methods: This facility-based cross-sectional study used a quality improvement approach to assess TI in hypertension management. Conducted following ethical approval per ICMR and Helsinki guidelines, it involved patient interviews, duplicate BP measurements and anonymised physician feedback. Patients with known hypertension were selected via stratified systematic random sampling, with outpatient department (OPD) tickets screened for eligibility. TI was defined by persistently elevated BP without therapeutic escalation. Sample size estimation, based on prior prevalence data, determined a requirement of 246 patients, with 278 patient samples and 51 physician samples collected (Fig 1). Data on demographics, adherence, BP readings and prescription patterns were gathered. Provider assessments included vignette-based evaluations to distinguish TI from clinical myopia. Statistical analysis using JASP 0.18.3 compared TI prevalence across subgroups, with significance testing and trend analysis. Quality improvement measures (repeat BP measurement and structured provider feedback) were implemented and monitored over 4 weeks to assess feasibility and impact in a busy outpatient setting. Results and discussion: This cross-sectional study assessed TI in hypertension management using a quality improvement framework. Among 278 patients, 177 (63.7%) had congruent BP readings, while 101 (36.3%) exhibited incongruent values, suggesting white-coat hypertension or transient BP elevation. Despite elevated BP, 53 (29.9%) patients in the congruent group experienced TI due to the absence of therapeutic escalation. When patient adherence was disregarded, TI increased to 49.7%. The total error rate in BP management ranged from 53.29% to 61.5%. TI was observed irrespective of patient-related factors, suggesting provider-related barriers have a critical role. These findings align with global studies, where TI prevalence ranges from 30% in India to 87% in the Netherlands.5 The progressive reduction in TI with physician audits highlights the role of feedback in improving hypertension control. Given TI’s contribution to stroke and ischaemic heart disease risk, integrating standardised BP protocols, physician decision support tools and structured follow-up can enhance global hypertension management.6 Addressing provider-related barriers is crucial for optimising treatment adherence and reducing cardiovascular mortality. Conclusion: To conclude, our study identified therapeutic inertia as being operable in a significant proportion of individuals. This has implications as far as overall BP control is concerned. The study estimates that such quality improvement methods are feasible, impactful, low-cost, scalable measures to improve hypertension management and physician and patient adherence to guidelines. The approach is simple and low cost, making it a viable option to be scaled to other non-communicable diseases across various OPDs of busy hospitals.